The Applied Law and Economics of Public Procurement. - Piga, Gustavo (Economics of legal relationships., 2013)
This book explores Public Procurement novelties and challenges in an interdisciplinary way. The process whereby the public sector awards contracts to companies for the supply of works, goods or services is a powerful instrument to ensure the achievement of new public goals as well as an efficient use of public funds. This book brings together the papers that have been presented during the ""First Symposium on Public Procurement"", a conference held in Rome last summer and to be repeated again yearly. As Public Procurement touches on many fields (law, economics, political science, engi.